(untitled) (PROKLA. Journal of Critical Social Science, 2024)
In this article, the highly controversial thesis of the state of Israel and the Zionist movement as phenomena of »settler colonialism« is discussed. Three paradigms of the term can be distinguished: firstly, the historical Zionist movement as a supposed form of settler colonialism, secondly, contemporary Israel as a settler-colonial state and thirdly, the view of individual Israelis as »settlers«.